Growth response of tissue culture-derived bamboo (Bambusa tulda Roxb.) Plantlets to sources and levels of inorganic nitrogen - Arradaza, Catherine C.; Modina, Antoneth A.; Ramos, Arsenio D.; Moreno, Rafonselle M. (Annals of Tropical Research, 2024)
Information on nitrogen nutrition of bamboo plants during the nursery stage is very limited. The study was conducted to generate more information regarding the nitrogen nutrition of bamboo (Bambusa tulda Roxb.) specifically to evaluate the effect of forms and levels of N on the early growth stage performance of tissue culture-derived bamboo plantlets and identify the best form and optimum level of nitrogen for bamboo plants during the nursery stage. The acclimatized tissue culture-derived bamboo (Bambusa tulda Roxb.) plantlets were grown in black polyethylene bags measuring 24x15cm containing potting medium composed of 1:1v/v mixture of garden soil and rice hull charcoal. These were applied with two forms of nitrogen (N1-nitrate-N and N2-ammonium-N) which served as the factor A and 3 levels of nitrogen (L1-0g N plant-1, L2-0.25g N plant-1, and L3-0.50g N plant-1 which was the factor B of a 2×3 factorial RCBD experiment. The effects of the treatments on the performance of the bamboo plantlets were evaluated by gathering growth parameters such as height, number of leaves and culms and leaf size, and dry weights of leaf, stem, root, and total biomass weight. The form of N applied did not significantly influenced the size of bamboo plants but significantly affected the plant dry weight. Plants fertilized with ammonium-N produced heavier biomass weight than those applied with nitrate-N. The levels of N-application significantly influenced both the plant size and weight. Application of 0.25g N and 0.5g N plant-1 significantly increased the number of culms and leaves and total plant biomass dry weight. Based on the effect on the size and weight of plants, application of 0.25g N plant-1 was already optimum for bamboo plants during the nursery stage. For bamboo plants at the nursery stage, ammonium-N was better than nitrate-N with 0.25g N plant-1 as the optimum level of application.